The SoV Probit - Brazell, Jeff (Henry Stewart Talks, 2010)
Source of volume and cannibalization, Product and line optimization questions, Quick definitions, Red bus / blue bus example, What is IID? and IIA?, We know IIA/IID gets source-of-volume wrong, When should we care about substitution patterns?, Source of volume calculations, Cannibalization = Preference, How do you "handle" IIA in your choice models?, Simulating preference shares: state-of-the-art, What does proportional substitution look like?, Industry survey: how do current methods do?, The SoV Probit, Why should I care about correlated errors?, Why aren't we all using Probit models?, A structured covariance Probit, Distance metrics, Choice experiment, Model fit statistics, Parameter estimates, WTP comparison, Representative correlation matrix, Does it work?